Education and professional strengthening of the community health agent - an ethnography study - Margareth S. Zanchetta; Ligia Costa Leite; Michel Perreault; Hélène Lefebvre (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2005)
This inquiry explored the educative actions of Community health agents (CHAs) with socially disaffiliated populations in a Rio de Janeiro metropolitan area. Individual and group interviews, participant observation during visits to the shantytowns, and picture gathering apprehended the philosophical and empirical dimensions of such actions. The software ATLAS ti. 4.2 supported the coding procedures of the raw material. Abduction in communication framed findings' analysis and interpretation. Analysis revealed their social professional identity, political awareness regarding their own organization as a professional group, plus criticisms regarding the negligence of occupational safety and the lack of governmental help. CHAs "voice" is a tool of social leadership and a main facilitator to empower the population, and to promote optimization of the health care system. Since their professional practice revealed conflicts, contradictions and paradoxes, it seems necessary a collective reflection on the needed support to sustain CHAs wishes for change and freedom to act.